The application of the associative mean spherical approximation in the theory of nonaqueous electrolyte solutions - Barthel, J.; Krienke, H.; Holovko, M.F.; Kapko, V.I.; Protsykevich, I.A. (Condensed Matter Physics, 2000)
Ionic association in electrolyte solutions is investigated in the framework of
chemical models. The associative mean spherical approximation (AMSA)
for electrolyte theory is reviewed. It is shown that AMSA in combination
with the Ebeling association constant satisfactorily reproduces the thermodynamic measurement data up to high concentrations for nonaqueous
solutions of solvents of relative permittivities in the range 20 < ε < 36 . For
ionic solutions of lower permittivity the AMSA is modiﬁed by including ion
trimers and tetramers to obtain a correct description of osmotic coefﬁcients
and ionic conductivities. Іонна асоціація в розчинах електролітів досліджується в рамках хімічних моделей. Дано огляд асоціативного середньосферичного наближення (АССН) в теорії електролітів. Показано, що АССН у комбінації з асоціативною константою Ебелінга задовільно відтворює дані
термодинамічних вимірювань, включаючи область високих концентрацій, для неводних розчинів електролітів з розчинниками з діелектричною проникністю в області 20 < ε < 36 . Для іонних розчинів з
низькою діелектричною проникністю АССН модифіковане включенням іонних тримерів і тетрамерів, щоб отримати правильний опис осмотичних коефіцієнтів та іонних провідностей.